Optimalisasi Wakaf Produktif sebagai Instrumen Keuangan Islam untuk Pembangunan Berkelanjutan - Rahman, Ĺalu Rohadi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Productive waqf represents a significant Islamic economic instrument with great potential to support sustainable economic development through the optimization of waqf assets for community empowerment. This article presents a literature review on the strategic role of productive waqf in enhancing social and economic welfare, as well as its implementation models across various sectors such as education, health, agriculture, and the environment. The research method employed is a systematic literature review with strict inclusion criteria to ensure the relevance and quality of the sources. The findings indicate that productive waqf is capable of creating added value and supporting the achievement of the Sustainable Development Goals (SDGs) through innovative and collaborative approaches involving waqf institutions, the government, and the private sector. However, productive waqf still faces several challenges, including low waqf literacy, suboptimal regulations, and less professional management practices. Therefore, strengthening strategies are required through education, policy development, and innovation in waqf products to maximize its potential. In conclusion, productive waqf should not be viewed merely as a financing instrument but as a fundamental pillar in building an inclusive and equitable socio-economic development framework. The integrated development of productive waqf is expected to enhance its contribution as a driving force for sustainable economic development in Indonesia and other countries with Islamic economic foundations.